EO aided comprehensive flood management for the Brahmaputra and Barak river basin in NE India - S. P. Aggarwal; D. Barman; S. S. Kundu; S. Kurbah; R. Das (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2025)
Floods are among the most frequent and devastating natural disasters globally, affecting over 94 million people annually. In Northeast India, particularly in Assam, recurrent floods caused by excessive rainfall, silt deposition causing reduction in river depth, rapid urbanization, and settlements in floodplains lead to significant economic and human losses. The Brahmaputra and Barak river basins with its complex hydrology, faces escalating flood risks due to climate change, highlighting the need for robust flood management systems. This study outlines a comprehensive flood management strategy for these basins integrating early warning systems, flood hazard zonation, and embankment breach monitoring. A Weather Research and Forecasting (WRF) model was employed to generate high-resolution rainfall forecasts, which was validated with satellite-based rainfall datasets. Hydrological modeling using HEC-HMS was conducted for all major tributaries, combining meteorological inputs to estimate river discharge and predict flood probabilities, achieving 80% to 90% success rate with a lead time of 36 to 48 hours. Alerts are disseminated to the authorities through emails and SMS. Embankment breach monitoring using satellite data identified vulnerable points along Assam’s rivers, aiding authorities in proactive flood mitigation. Additionally, flood hazard zonation maps prepared using remote sensing could delineate high-risk areas, supporting long-term structural planning. These efforts demonstrate the effective use of earth observation data, numerical modeling, and in situ measurements in flood mitigation. Despite limitations in meteorological and hydrological models, this system provides critical early warnings, minimizing flood impacts. This integrated approach serves as a model for flood-prone regions globally, emphasizing the importance of advanced technologies and timely interventions in disaster management.